2006
DOI: 10.1523/jneurosci.5326-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Interaction between NR2B and MAGUK in l-DOPA Induced Dyskinesia

Abstract: Abnormal function of NMDA receptor has been suggested to be correlated with the pathogenesis of Parkinson's disease (PD) as well as with the development of L-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesia. Here we show that NMDA receptor NR2 subunits display specific alterations of their subcellular distribution in striata from unilateral 6-hydroxydopamine-lesioned, L-DOPA-treated dyskinetic, and L-DOPA-treated nondyskinetic rats. Dyskinetic animals have significantly higher levels of NR2A subunit in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
194
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(213 citation statements)
references
References 36 publications
(63 reference statements)
15
194
0
4
Order By: Relevance
“…As previously reported [25], TIF has been used instead of the classical post-synaptic density (PSD) because the amount of the starting material was very limited.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported [25], TIF has been used instead of the classical post-synaptic density (PSD) because the amount of the starting material was very limited.…”
Section: Western Blottingmentioning
confidence: 99%
“…Using a well-established post-synaptic-enriched biochemical preparation [25], we isolated the triton insoluble fraction from pharmacological treated brain slices. In line with previous results [34], we found that the levels of p-GluA1/GluA1 ratio were significantly increased upon DHPG treatment compared to control (control n = 4 vs. DHPG n = 4; p < 0.01) (Fig.…”
Section: Pctx1 Does Not Affect Polyphosphoinositide Hydrolysis But Prmentioning
confidence: 99%
“…Interestingly, MAO-B inhibitors have been shown to partially protect neurons against overactivation of NMDA receptors without interfering with their physiological function (Niittykoski et al, 2003). This is intriguing since NMDA receptor is altered in experimental parkinsonism (Dunah and Standaert, 2001;PaillĂ© et al, 2010), during development of L-DOPA induced dyskinesia (Gardoni et al, 2006) and in patients (Calon et al, 2003). In addition, synaptic localization of NMDA receptor subunits, namely NR2A and NR2B, and their functional interactions with scaffolding elements of the PSD-MAGUK protein family have been shown to be crucial to the pathogenesis of Parkinson's disease and to the development of L-DOPA induced dyskinesia (Gardoni et al, 2006;Picconi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is intriguing since NMDA receptor is altered in experimental parkinsonism (Dunah and Standaert, 2001;PaillĂ© et al, 2010), during development of L-DOPA induced dyskinesia (Gardoni et al, 2006) and in patients (Calon et al, 2003). In addition, synaptic localization of NMDA receptor subunits, namely NR2A and NR2B, and their functional interactions with scaffolding elements of the PSD-MAGUK protein family have been shown to be crucial to the pathogenesis of Parkinson's disease and to the development of L-DOPA induced dyskinesia (Gardoni et al, 2006;Picconi et al, 2004). In a rat model of early Parkinson's disease, normalization of the aberrant synaptic localization of NR2A subunits rescued the motor symptoms (PaillĂ© et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the discrete pre-and postsynaptic, and intraand extrasynaptic, localization of the various receptor subunits (Bernard and Bolam, 1998;Wang and Pickel, 2000;Dunah and Standaert, 2003;Galvan et al, 2006), striatal NMDA receptor stimulation has multiple and complex functional effects. Moderate activation of NMDA receptors controls, for example, monoaminergic, cholinergic, glutamatergic and peptidergic neurotransmission (Becquet et al, 1990;Young and Bradford, 1993;Knauber et al, 1999;Hathway et al, 2001;Radke et al, 2001;Marti et al, 2005) and, as a consequence, affects synaptic plasticity (Centonze et al, 2004;Dang et al, 2006), motor function (Hallett et al, 2005;Gardoni et al, 2006) and cellular bioenergetics (Moncada and Bolanos, 2006 Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript.…”
Section: Introductionmentioning
confidence: 99%